Estrategias lúdicas y la educación financiera enfocada en los gastos e ingresos en niños de primer año de preparatoria de la unidad educativa “Victoria Vásconez Cuvi”. - Iza Ronquillo, Mishell Abigail (2023)
The present research arises after analyzing international contexts in which financial education is studied from the first years, having great results in the generation of a culture of planning of expenses and income, The problem is presented in the initial education curriculum in Ecuador that focuses on knowledge that does not land in aspects related to the generation of a culture in these aspects at an early age. The objective was to analyze financial education focused on expenses and income through playful strategies in the first year of high school children of the Victoria Vásconez Cuvi Educational Unit. Taking into account that this methodology encourages early learning based on active and fun participation. This research had a mixed approach where a situational diagnosis was made on the use of resources for financial education education, through surveys of parents, interviews with teachers and an observation sheet applied to the implementation of the proposal. According to the interview it was determined that teachers do not approach financial education with an equally important focus as other areas, which has limited the development of financial skills in children. Also, it was found that 84% of parents do not know about the playful strategies that are applied in the classroom. Reason why, the proposal was designed; "The fun side of Finance Educa+Gasta-": practical workshops for financial education with the application of playful strategies in which didactic and environmental material was used, improving students' financial skills and fostering meaningful learning and comprehensive growth of children in the area of financial education.